Inhibition of voltage-gated sodium channels by sumatriptan bioisosteres - Carbonara, Roberta; Carocci, Alessia; Roussel, Julien; Crescenzo, Giuseppe; Buonavoglia, Canio; Franchini, Carlo; Lentini, Giovanni; Camerino, Diana Conte; Desaphy, Jean-François (Frontiers in Pharmacology, 2015)
Voltage-gated sodium channels are known to play a pivotal role in perception and transmission of pain sensations. Gain-of-function mutations in the genes encoding the peripheral neuronal sodium channels, hNav1.7-1.9, cause human painful diseases. Thus while treatment of chronic pain remains an unmet clinical need, sodium channel blockers are considered as promising druggable targets. In a previous study, we evaluated the analgesic activity of sumatriptan, an agonist of serotonin 5HT1B/D receptors, and some new chiral bioisosteres, using the hot plate test in the mouse. Interestingly, we observed that the analgesic effectiveness was not necessarily correlated to serotonin agonism. In this study, we evaluated whether sumatriptan and its congeners may inhibit heterologously-expressed hNav1.7 sodium channels using the patch-clamp method. We show that sumatriptan blocks hNav1.7 channels only at very high, supratherapeutic concentrations. In contrast, its three analogues, namely 20b, (R)-31b, and (S)-22b, exert a dose and use-dependent sodium channel block. At 0.1 and 10 Hz stimulation frequencies, the most potent compound, (S)-22b, was 4.4 and 1.7 fold more potent than the well-known sodium channel blocker mexiletine. The compound induces a negative shift of voltage dependence of fast inactivation, suggesting higher affinity to the inactivated channel. Accordingly, we show that (S)-22b likely binds the conserved local anesthetic receptor within voltage-gated sodium channels. Combining these results with the previous ones, we hypothesize that use-dependent sodium channel blockade contributes to the analgesic activity of (R)-31b and (S)-22b. These later compounds represent promising lead compounds for the development of efficient analgesics, the mechanism of action of which may include a dual action on sodium channels and 5HT1D receptors.